DOI: 10.14264/uql.2015.1005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an inquiry-based learning using interactive simulations for enhancing students’ conceptual understanding in physics

Abstract: Two mixed-methods studies (a pilot study and a main study) were carried out to investigate the effectiveness of a novel inquiry-based learning method (named the Inquiry-based learning with Interactive Simulation -ILIS approach). The studies focused on 10 th grade students' conceptual understandings about force and motion in physics. In each of the studies, an explanatory mixed methods design was adapted to combine a quantitative phase with a qualitative phase. The initial quantitative phase employed a quasi-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 234 publications
0
2
1
1
Order By: Relevance
“…This further implies that the developed and validated guided IBL materials can be used as alternative learning materials. These results contrast those of previous studies by Koksal and Berberoglu (2012), Duran and Dokme (2016), Abdi (2014), Aulia et al (2018), Cooper, Bailey, andBriggs (2015), Brune (2010), Ferguson (2010, Fan (2015) who regarded IBL more effective than non-IBL approach like the conventional method. However, Lynn (2012) supports the results of this study with her finding that students learn equally and effectively through both inquiry-based and traditional teaching.…”
Section: Instruction Along Levels Of Cognitive Domaincontrasting
confidence: 90%
“…This further implies that the developed and validated guided IBL materials can be used as alternative learning materials. These results contrast those of previous studies by Koksal and Berberoglu (2012), Duran and Dokme (2016), Abdi (2014), Aulia et al (2018), Cooper, Bailey, andBriggs (2015), Brune (2010), Ferguson (2010, Fan (2015) who regarded IBL more effective than non-IBL approach like the conventional method. However, Lynn (2012) supports the results of this study with her finding that students learn equally and effectively through both inquiry-based and traditional teaching.…”
Section: Instruction Along Levels Of Cognitive Domaincontrasting
confidence: 90%
“…According to Duran (2016) IBSE increases students' critical thinking in science. The use of IBL in teaching and learning has positive implications as it helps students to boost their conceptual understanding in motion and force (Fan, 2015).…”
Section: An Overview On Inquiry-based Science Education (Ibse)mentioning
confidence: 99%
“…Science education researches in general and physics education researches in particular have demonstrated that quality physics instruction is a challenge both in the developed and developing nations (Mbonyiryivuze et al, 2019). One of the most prominent contributions of physics education researches was its finding that shed light on the failure of traditional instruction focused on rote learning, mere memorization, and naïve quantitative problem solving in teaching introductory physics courses which do not bring conceptual understanding of physics concepts, principles and laws (Fan, 2015;Gerace & Beatty, 2005). Many students completed their study of physics with severe gaps in their conceptual understanding of concepts in many physics topics in a traditional instruction regardless of physics teachers' efforts (Eshetu & Alemu, 2018;Cahyadi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…That is, in one hand, traditional teaching approaches lead to problems of misconceptions and inadequate conceptual understanding in physics concepts, on the other hand; many of the students remain with inadequate explanation of physics concepts after completing traditional instruction. This is because students learn very little from traditional lecture type instruction and it does not encourage them to think by themselves in constructing their own meaning and learning (Fan, 2015;Lasry et al, 2014). The question of quality physics education is still a concern which is continued to the present time.…”
Section: Introductionmentioning
confidence: 99%